C1,α Regularity of Viscosity Solutions of Fully Nonlinear Parabolic PDE Under Natural Structure Conditions (Journal of Partial Differential Equations, 1999)
In this paper, we concern the fully nonlinear parabolic equations u_t + F(x, t , u, Du, D² u) = 0. Under the natural structure conditions as that in [1], we obtain the C^{1,α} estimates of the viscosity solutions.
Keywords: Fully nonlinear parabolic equations; C^{1; α} regularity; viscosity solulions